Accumulating Data to Optimally Predict Obesity Treatment (ADOPT) Core Measures: Environmental Domain. (25th March 2018) - Saelens, Brian E.; Arteaga, S. Sonia; Berrigan, David; Ballard, Rachel M.; Gorin, Amy A.; Powell‐Wiley, Tiffany M.; Pratt, Charlotte; Reedy, Jill; Zenk, Shannon N.
Abstract : Background: There is growing interest in how environment is related to adults' weight and activity and eating behaviors. However, little is known about whether environmental factors are related to the individual variability seen in adults' intentional weight loss or maintenance outcomes. Objectives: The environmental domain subgroup of the Accumulating Data to Optimally Predict obesity Treatment (ADOPT) Core Measures Project sought to identify a parsimonious set of objective and perceived neighborhood and social environment constructs and corresponding measures to include in the assessment of response to adult weight‐loss treatment. Significance: Starting with the home address, the environmental domain subgroup recommended for inclusion in future weight‐loss or maintenance studies constructs and measures related to walkability, perceived land use mix, food outlet accessibility (perceived and objective), perceived food availability, socioeconomics, and crime‐related safety (perceived and objective) to characterize the home neighborhood environment. The subgroup also recommended constructs and measures related to social norms (perceived and objective) and perceived support to characterize an individual's social environment. The 12 neighborhood and social environment constructs and corresponding measures provide a succinct and comprehensive set to allow for more systematic examination of the impact of environment on adults' weight loss and maintenance.